Hubungan Beberapa Faktor Produksi dan Salinitas Terhadap Produktivitas Padi Sawah (Oryza sativa L.) di Desa Rugemuk, Kecamatan Pantai Labu - Ropikoh Hasibuan; Supriadi Supriadi; Mariani Sembiring (Universitas Sumatera Utara, 2019)
ABSTRACT Rice is a plant that is classified as vulnerable to the maternity environment so that it can reduce productivity. The efficient use of production factors can increase maximum profits for rice production. This study aims to determine the impact of extensive land area, fertilizer application, pesticide on the productivity of paddy rice, to determine the limits of salinity land suitability to productivity of paddy rice. This research was conducted in Rugemuk Village, Pantai Labu District and Laboratory of Chemical and Soil Fertility, Research and Technology, Faculty of Agriculture, University of North Sumatra in July-September 2018. This study uses a purposive sampling method. The parameters measured were extensive of land area, N fertilizer, P fertilizer, K fertilizer, pesticide, salinity and productivity of lowland rice. Data were tested by regression analysis and correlation.The results showed the that : simultaneously the extensive of land area, N fertilizer, P fertilizer, K fertilizer and pesticide are positively correlated to the productivity of paddy rice, in partially salinity correlates negatively to the productivity of paddy rice. Limit the suitability of land for salinity rice between the classes in suitable with unsuitable is 3.74 dS/m. Keywords: lowland rice, factors of production, salinity, land suitability, productivity